Epigenetics Theoretical Limits of Synthetic Genomes : The Cases of Artificials Caulobacter (C. eth-2.0), Mycoplasma Mycoides (JCVI-Syn 1.0, JCVI-Syn 3.0 and JCVI_3A), E-coli and YEAST chr XII (Global Journal of Science Frontier Research, 2022)
In Venetz et al 2019 authors rebuilt the essential genome of Caulobacter crescentus through the process of chemical synthesis rewriting and studied the genetic information content at the level of its essential genes Then they reduced the native Caulobacter crescentus native Caulobacter NA1000 genome sequence real genome 4042929 bp to the 785 701-bp reduced synthetic genome Here we demonstrate the existence of a palindromic-like mirror structure that exists in real genomes and disappears totally in the synthetic genome This biomathematic meta-organization is based on characteristic proportions of Fibonacci numbers between DNA single strand nucleotides proportions TC AG on the one hand and TG AC on the other hand In both cases we suggest that this meta-structure enhances the threedimensional cohesion of the two DNA strands of the genome We then generalize this study to the different synthetic genomes and synthetic cells published by the Craig Venter Institute on Mycoplasma Mycoides JCVI-syn1 0 in 2010 JCVI-syn3 0 in 2016 and JCVI-syn3A in 2019 Finally in the discussion section we extend this study to synthetic genomes of E-Coli and Yeast chromosome XII
Keywords: synthetic genomes; epigenetics; transposons; biomathematics; fibonacci numbers